Индивидуальная, межсезонная и географическая изменчивость окраски яиц серого журавля: предложение новой методики. Сообщение 1. Индивидуальная изменчивость окраски яиц - Винтер, С.В. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2007)
In a long-term study (1989-2002) of the Common Crane (Grus grus) biology on three study areas in Eastern Ukraine a new method of describing the colouration and the micro-relief of the egg-shell surface was developed, following Kostin (1977). A total of 319 eggs in 171 clutches of free-living birds was studied. This is the largest sample so far. Up to 107 characters of each egg were documented and frequencies compared between studies and years. Cообщение II, включая список цитируемой литературы, будет опубликовано вследующих выпусках сборника “Бранта”. This paper will be continued with Communication 2 in next issues of “Branta” and added with refernces.